Protein Glycation in Plants—An Under-Researched Field with Much Still to Discover - Rabbani, Naila (Int J Mol Sci, 2020)
Recent research has identified glycation as a non-enzymatic post-translational modification of proteins in plants with a potential contributory role to the functional impairment of the plant proteome. Reducing sugars with a free aldehyde or ketone group such as glucose, fructose and galactose react with the N-terminal and lysine side chain amino groups of proteins. A common early-stage glycation adduct formed from glucose is N(ε)-fructosyl-lysine (FL). Saccharide-derived reactive dicarbonyls are arginine residue-directed glycating agents, forming advanced glycation endproducts (AGEs). A dominant dicarbonyl is methylglyoxal—formed mainly by the trace-level degradation of triosephosphates, including through the Calvin cycle of photosynthesis. Methylglyoxal forms the major quantitative AGE, hydroimidazolone MG-H1. Glucose and methylglyoxal concentrations in plants change with the developmental stage, senescence, light and dark cycles and also likely biotic and abiotic stresses. Proteomics analysis indicates that there is an enrichment of the amino acid residue targets of glycation, arginine and lysine residues, in predicted functional sites of the plant proteome, suggesting the susceptibility of proteins to functional inactivation by glycation. In this review, we give a brief introduction to glycation, glycating agents and glycation adducts in plants. We consider dicarbonyl stress, the functional vulnerability of the plant proteome to arginine-directed glycation and the likely role of methylglyoxal-mediated glycation in the activation of the unfolded protein response in plants. The latter is linked to the recent suggestion of protein glycation in sugar signaling in plant metabolism. The overexpression of glyoxalase 1, which suppresses glycation by methylglyoxal and glyoxal, produced plants resistant to high salinity, drought, extreme temperature and other stresses. Further research to decrease protein glycation in plants may lead to improved plant growth and assist the breeding of plant varieties resistant to environmental stress and senescence—including plants of commercial ornamental and crop cultivation value.